Diaper-embedded urine test device for the screening of urinary tract infections in children: a cohort study - Niko Paalanne; Lotta Wikstedt; Tytti Pokka; Jarmo Salo; Matti Uhari; Marjo Renko; Terhi Tapiainen (BMC, 2020)
Abstract Background There is a need for an easy and sensitive method for screening of urinary tract infections in young children. We set out to test whether a novel diaper-embedded urine test device is feasible and reliable in screening for urinary tract infections. Methods This prospective cohort study consisted of young children examined due to a suspected acute urinary tract infection at the Pediatric Emergency Department of the Oulu University Hospital, Finland. We analyzed the same urine samples using three different methods: 1) a diaper-embedded test device applied to the urine pad within the diaper, 2) a urine sample aspirated from the urine pad for the conventional point-of-care dipstick test, and 3) a urine sample aspirated from the urine pad and analyzed in the laboratory with an automated urine chemistry analyzer. The gold standard for confirming urinary tract infection was quantitative bacterial culture. Results Urine samples were available from 565 children. Bacterial culture confirmed urinary tract infection in 143 children. Sensitivity of the positive leukocyte screening of the diaper-embedded urine test device was 93.1% (95% CI: 87.4-96.8) and that of the point-of-care urine dipstick analysis was 95.4% (90.3-98.3) in those with both tests results available (n = 528). The sensitivity of the positive leukocyte test of the diaper-embedded test device was 91.4% (85.4-95.5) and that of the automated analysis was 88.5% (82.0-93.3) in those with both tests available (n = 547). The time to the test result after urination was immediate for the diaper-embedded test, 1-5 min for point-of-care dipstick, and 30-60 min for laboratory-based automated urine chemistry analyzer. Conclusions In this prospective study, the diaper-embedded urine test device was an easy and sensitive screening method for UTIs in young children. The main clinical benefit of the diaper-embedded urine test device was that the screening test result was available immediately after urination.